PENGEMBANGAN MEDIA INTERAKTIF PEMBELAJARAN COMPUTATIONAL THINKING “JEJAKLOGIKA” UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP - Adipura, Laksamana; Handayani, Anik; Srini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Computational Thinking (CT) is a fundamental problem-solving approach in the digital era, involving skills such as decomposition, pattern recognition, abstraction, and algorithmic thinking. This study aims to develop an interactive learning media called JejakLogika, designed to enhance junior high school students’ critical thinking skills through the CT approach. The research employed a Research and Development (R&D) methodology using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and was conducted with seventh-grade students at SMPN 22 Malang. Validation results indicated that the learning media received an